2017
DOI: 10.1186/s13063-017-2275-y
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, double-blind, placebo-controlled trial of minocycline and/or omega-3 fatty acids added to treatment as usual for at-risk mental states (NAYAB): study protocol

Abstract: BackgroundThe at-risk mental state (ARMS) describes individuals at high risk of developing schizophrenia or psychosis. The use of antipsychotics in this population is not supported, because most individuals with ARMS are unlikely to develop psychosis. Anti-inflammatory treatments and polyunsaturated fatty acids (PUFAs) may have some beneficial effects in the treatment of ARMS. There have been no controlled clinical trials in which researchers have investigated the use of minocycline for ARMS and no trials invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
4
0
2
Order By: Relevance
“…In this sense, MIN improved the negative symptoms in early-phase ( Liu et al, 2014 ) or persistent schizophrenia ( Khodaie-Ardakani et al, 2014 ; Kelly et al, 2015 ), and it also improved working memory, anxiety, and depression ( Kelly et al, 2015 ), but its preventive potential has only recently been explored in humans. In this respect, only 1 study addresses a 6-month intervention with MIN added to regular treatment in individuals at risk of developing schizophrenia or psychosis ( Qurashi et al, 2017 ), although no results have been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, MIN improved the negative symptoms in early-phase ( Liu et al, 2014 ) or persistent schizophrenia ( Khodaie-Ardakani et al, 2014 ; Kelly et al, 2015 ), and it also improved working memory, anxiety, and depression ( Kelly et al, 2015 ), but its preventive potential has only recently been explored in humans. In this respect, only 1 study addresses a 6-month intervention with MIN added to regular treatment in individuals at risk of developing schizophrenia or psychosis ( Qurashi et al, 2017 ), although no results have been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosis is one of the 20 leading causes of disability worldwide, affecting 29 million people [ 71 ] contributing to major burden in LMIC. Global health research has now started to receive due attention from funders in high income countries and there are ongoing studies in ARMS in LMIC [ 72 ]. Research covering a wider range of settings and across LMIC is needed to ensure decision makers have evidence relevant to their locality.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome of the NAYAB study was transition to psychosis at 12 months. The detailed methodology of the primary study has been described in the published protocol (Qurashi et al, 2017). In this cross‐sectional secondary analysis, we sought to investigate the prevalence of depressive and suicidal ideation in people with ARMS using data collected from the Montgomery and Asberg Depression Rating Scale (MADRS) (Montgomery & Asberg, 1979).…”
Section: Methodsmentioning
confidence: 99%